PERLINDUNGAN HUKUM TERHADAP PEKERJA AKIBAT PEMUTUSAN HUBUNGAN KERJA (PHK) SEPIHAK BERDASARKAN UNDANG-UNDANG NOMOR 13 TAHUN 2003 TENTANG KETENAGAKERJAAN (STUDI PUTUSAN PENGADILAN NEGERI BANDUNG NOMOR 211/PDT.SUS-PHI/2018/PN.BDG) - Grace Angelia; Andari Yurikosari (Jurnal Hukum Adigama, 2020)
Termination of Employment is one of the disputes that often arises in the world of work. This certainly can be detrimental to the workers because in addition to losing their jobs for their lives, workers often do not get their rights in accordance with the provisions stipulated in the Manpower Act especially if the worker does not make a mistake in the company. Layoff disputes can be resolved through bipartite, tripartite, to court level. In this case, 9 (nine) workers who were laid off for efficiency reasons had made bipartite negotiations and mediation efforts but still did not reach an agreement so that the workers filed a lawsuit with the Bandung District Court. Even so, workers still do not get their rights in accordance with the provisions of the law so that if seen in this decision the role of the law as a legal umbrella to protect the rights of the community is not realized.